Hypoxemia and acute mountain sickness: Which comes first? - Loeppky, J. A.; Icenogle, M. V.; Charlton, G. A.; Conn, C. A.; Maes, D.; Riboni, K.; Gates, L.; Vidal Melo, M. F.; Roach, R. C. (High Altitude Medicine & Biology, 2008)
Hypoxemia is usually associated with acute mountain sickness (AMS), but most studies have varied in time and magnitude of altitude exposure, exercise, diet, environmental conditions, and severity of pulmonary edema. We wished to determine whether hypoxemia occurred early in subjects who developed subsequent AMS while resting at a simulated altitude of 426 mmHg (˜16,000 ft or 4880 m). Exposures of 51 men and women were carried out for 8 to 12 h. AMS was determined by Lake Louise (LL) and AMS-C scores near the end of exposure, with spirometry and gas exchange measured the day before (C) and after 1 (A1), 6 (A6), and last (A12) h at simulated altitude and arterial blood at C, A1, and A12. Responses of 16 subjects having the lowest AMS scores (nonAMS: mean LL = 1.0, range = 0-2.5) were compared with the 16 having the highest scores (+AMS: mean LL = 7.4, range = 5-11). Total and alveolar ventilation responses to altitude were not different between groups. +AMS had significantly lower PaO2 (4.6 mmHg) and SaO2 (4.8%) at A1 and 3.3 mmHg and 3.1% at A12. Spirometry changes were similar at A1, but at A6 and A12 reduced vital capacity (VC) and increased breathing frequency suggested interstitial pulmonary edema in +AMS. The early hypoxemia in +AMS appears to be the result of diffusion impairment or venous admixture, perhaps due to a unique autonomic response affecting pulmonary perfusion. Early hypoxemia may be useful to predict